Development of Digital-Based Learning Modules Using the Microlearning Method to Improve Mathematical Literacy Skills for 7th Graders at SMP Swasta Bina Bersaudara Medan - Friska Paulina Simanjuntak; Denny Haris (Asian Journal of Applied Education (AJAE), 2023)
The purpose of this research is to produce learning media products in the form of digital-based learning modules using valid, practical, and effective microlearning methods on Lines and Angles. This research uses a type of development research with the development model used, namely the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were 30 students of class VII-1 at Bina Bersaudara Private Middle School Medan. While the object of this study is a digital-based learning module using the microlearning method. The results in this study indicate that: (1) The validity of the learning module based on the assessment of material experts and media experts obtained an average score of 89.29% and 89.76% in the valid category. (2) The practicality of the learning module based on the results of the teacher's assessment is 92.5% with the criteria of 'very practical' and the practicality score based on the results of the student assessment is 92.4% with the criteria of 'very practical'. (3) The effectiveness of the learning module is obtained from the results of classical student mastery of 90.0%, the achievement of indicators of mathematical literacy is 85.42%, the learning time used does not exceed ordinary learning, and students respond positively to the learning module with an achievement of a percentage of 92.4% which fall into the 'very positive' category. Based on the research results, the development of digital-based learning modules using the microlearning method on Lines and Angles material can be said to be feasible with valid, practical, and effective categories.